Development of food composition database of Kelantanese foods - Harith, Sakinah; Razak, Shariza Abdul; Zainal, Nor Azmi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
This study was conducted to determine nutrient composition, based on foods, which are widely available and popular among the people of Kelantan. This study will be very important in establishing reliable data on the nutrient composition of foods consumed by the community. Hundred types of foods that are served in Kelantan had been chosen in this study. Food samples for analysis were purchased from three different places of production. Macronutrients such as calorie, carbohydrate, moisture, protein, fat and ash were analyzed using the standard methods of AOAC (1995). The results showed that the foods analyzed generally high in carbohydrate. Although these foods are high in carbohydrates, Kelantanese still able to consume them by controlling the amount of food intake. These results will be used in the estimation of nutrient intake in relation to study of diet and health relationship for Kelantan population.